Hubungan Kesehatan Gigi dan Mulut dengan Konsep Diri Pada Remaja di SMPN 7 Pariaman: The Relationship between Dental and Oral Health with Self-Concept in Adolescents at SMPN 7 Pariaman - Deswita; Tiara Mayastari; Atih Rahayuningsih (NERS Jurnal Keperawatan, 2013)
Self concept can be influenced by any changes of physical health, the maturation, the growth, and the sociocultural process. The dental and mouth health is one of the most common health problem of adolescent. The dental and mouthcleanliness, one of the self cleanliness, is influenced the component of self concept. This studywas designed to describe the correlation between mouth health and self concept of adolescent in junior high school number 7 Pariaman using the correlation with cross sectionaldesign. The sampling technique used wastheproportionate stratified random sampling that consists of 80 participants. The data were analyzed by using the spearman correlation test. For the results of study, 66,3% adolescentwas with unhealthy tooth and mouth, 72,5% had the positive self concept. The result of computer analysis shown the mouth health is associated to self concept of adolescent in junior high school number 7 Pariaman toward positive, moderate correlation strength, and significant (r= 0,408; p= 0,000). From the result, it can be suggested that healthy service institution must make a policy about the checking of tooth and mouth healthy periodically, providing information and the impact of tooth and mouth healthy by visiting school directly.